Constituição de identidade docente em memoriais de licenciandos do curso de Ciências Naturais e Matemática a distância da UAB – MT - Santana, Verondina Ferreira (2012)
This paper results from research developed at the Masters Course in Education of the University Campus Rondonópolis ─ UFMT and aims to investigate reflective registers in memorial of the undergraduates in training, which narrate about their perceptions of how is the process of building its identity over the teachers training to become a teacher in distance education course. For this proposal, the research took as its subject three licenciandas Course of Natural Science and Mathematics in Distance Education mode, the Open University of Brazil, in its pole located in the municipality of Pedra Preta - MT. The memorials fall within the field of autobiography and consists of important tools to analyze trajectories of training and reflective processes of the constitution of the future teacher professional identity, since it contains the "narrative self" of the guys who build them. The research questions are found in the students of Bachelor of Natural Sciences and Mathematics in distance education realize how is the construction of their identity through teacher training? How to describe this process and what are the contents that they consider significant for your training? What to tell about the process of constitution of identity in teaching distance learning courses in training memorials? The present study intends to contribute in the investigation into the construction of teacher identity in distance education courses with a focus on bringing information about UAB undergraduates in training path. Memorials analyzed, although consisting of a narrative of undergraduates in a year and a half allowed to observe the ongoing construction and re-constructions of the students in their educational process, their expectations and projections for the future profession and also check the perceptions and records that present on the constitution of identity in teaching courses in the distance.